Classification of Learners:Subjective Validation through Models - Athavale, Prashant A.; Kattimani, H. D. (Journal of Engineering Education Transformations, 2025)
This paper describes the learning models and their validation through the results of a study conducted on a group of students. The results do have a good correlation but the validity is to be established with further study over a period of time.